The Effect of Applying the Archerys ID Model Instructional Design on Moral Character, Ethics, and Learning Performance of High School Students in Physics Learning - Mutia Egica Putri; Darmansyah; Fetri Yeni; Zuwirna; Putri Syukriani; Maharani Rizky Pratiwi (Postgraduate, University of Mataram, 2024)
Academic dishonesty and students' inability to contextualize learning, particularly in physics, contribute to poor understanding. This study investigates the impact of the Archerys ID Model on students' moral character, ethics, and learning performance in physics. The model is expected to enhance moral and ethical values while improving learning performance compared to conventional methods. A quasi-experimental design with Nonequivalent Control Group was used, involving two classes: an experimental class using the Archerys ID Model and a control class using traditional methods. Pretests and posttests measured changes in moral character, ethics, and learning performance, and data were analyzed using an Independent T-Test. The independent T-Test analysis shows that the Archerys ID Model significantly enhances students' moral character, ethics, and learning performance in physics for grade XI at SMAN 12 Padang, with significance values of 0.032, 0.023, and 0.031, respectively. These findings indicate that the Archerys ID Model is more effective than the TPACK instructional design model in fostering character and academic outcomes.